The Role of Intellectual Capital in the Relationship between Good Corporate Governance, Financial Performance and Financial Distress - Jati , Ahmad Waluya; Kholmi, Masiyah; Jannah, Wardatul (Universitas Muhammadiyah Surakarta, 2023)
This study examines the effect of good corporate governance and financial performance on financial distress, with intellectual capital as a moderating variable. Good Corporate Governance, Financial Performance and Intellectual Capital are important tools that assure investors of the health of a business, thereby attracting interest to invest in companies that affect the capital to be obtained so as to increase company profits. Companies that are continuously able to make profits will avoid financial distress. This is due to the good management of the company, thereby increasing the value of the company. The sample in this study consisted of 150 observations from 75 manufacturing sector companies listed on the Indonesia Stock Exchange from 2020-2021. Manufacturing companies are the leading industry with the highest GDP contribution compared to other sectors. The Research result are derived from the multiple regression and MRA methods used in this study. Research results show that good corporate governance and financial performance have a positive effect on financial distress. Meanwhile, intellectual capital can strengthen the link between good corporate governance and financial distress. This research can support signal theory which can provide a good framework for understanding the impact of good corporate governance and financial performance on financial distress. This theory explains that companies, as senders of information (information owner), want to make the information relevant to the use of the information by the recipients or users most concerned.